О влиянии настройки контура скорости с пи-регулятором на устойчивость одномассовой электромеханической системы с отрицательным вязким трением - Клепиков, Владимир Борисович; Осичев, Александр Васильевич; Абдульмалик, Дж. С. (Харьковский государственный политехнический университет, 1997)
In this paper the influence of deviation of the contours parametrs on the distributions of the dynamic stability borders if one-mass electromechanical system with negative viscous friction and subordinated control system under symmetrical optimum was investigated. The analysis were carried out for three modificated models of the considered system.
Keywords: система подчиненного регулирования; электропривод; ПИ-регулятор; связь обратная